2015
DOI: 10.1095/biolreprod.114.124388
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Interstitial Cells in the Mouse and Monkey Female Reproductive Tracts1

Abstract: Growing evidence suggests important roles for specialized platelet-derived growth factor receptor alpha-positive (PDGFRalpha(+)) cells in regulating the behaviors of visceral smooth muscle organs. Examination of the female reproductive tracts of mice and monkeys showed that PDGFRalpha(+) cells form extensive networks in ovary, oviduct, and uterus. PDGFRalpha(+) cells were located in discrete locations within these organs, and their distribution and density were similar in rodents and primates. PDGFRalpha(+) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…It is distinct from smooth muscle cells and ICCs, and was characterized to have a variable gene expression between parts of the reproductive tract (e.g., ovary, oviduct, and uterus) or between the tissue regions of the same organ (e.g., uterine myometrium vs. endometrium) [ 131 ]. These cells are unlikely to provide pacemaker activity, as key pacemaker genes found in ICCs (e.g., Kit , and Ano1 ) [ 121 , 132 ] were not detected to be expressed, while the Gja1 gene encoding for connexin 43 was identified in high levels suggesting their possible involvement in forming gap junctions in between and with the neighboring smooth muscle cells [ 131 ]. CD34 and PDGFRα are considered as reliable markers to identify and separate TCs [ 47 , 133 , 134 ] and we might suppose that the newly identified interstitial cells are corresponding to TCs.…”
Section: Calcium Signaling In Tcsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is distinct from smooth muscle cells and ICCs, and was characterized to have a variable gene expression between parts of the reproductive tract (e.g., ovary, oviduct, and uterus) or between the tissue regions of the same organ (e.g., uterine myometrium vs. endometrium) [ 131 ]. These cells are unlikely to provide pacemaker activity, as key pacemaker genes found in ICCs (e.g., Kit , and Ano1 ) [ 121 , 132 ] were not detected to be expressed, while the Gja1 gene encoding for connexin 43 was identified in high levels suggesting their possible involvement in forming gap junctions in between and with the neighboring smooth muscle cells [ 131 ]. CD34 and PDGFRα are considered as reliable markers to identify and separate TCs [ 47 , 133 , 134 ] and we might suppose that the newly identified interstitial cells are corresponding to TCs.…”
Section: Calcium Signaling In Tcsmentioning
confidence: 99%
“…Oppositely to the uterine TCs that do not express the pacemaker-related Kit and Ano1 genes [ 131 ], cardiac TCs express CD34, CD29, vimentin, sca-1, c-kit, and Nanog, and are more likely to be involved in the heart pacemaking activity [ 133 , 139 , 140 ]. Additionally, cardiac TCs were demonstrated to functionally express large conductance Ca 2+ -activated K + currents (BKCa) and inwardly rectifying K + currents, but not transient outward K + currents or ATP-sensitive potassium current [ 124 ].…”
Section: Calcium Signaling In Tcsmentioning
confidence: 99%
“…; Peri et al . ), Myh11 (myosin heavy chain; smooth muscle cells), Uch11 encoding PGP 9.5 (nerve cells) and Tpsab1 ( mast cell tryptase). Enriched USMCs isolated from SMC‐eGFP + mice showed minimal expression of these genes with the exception of the smooth muscle marker Myh11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have sought to find an "ICC-like cell" in the uterus, searching for interstitial cells that produce similar slow waves or express similar membrane markers. So-called ICC-like cells have been found in the uterus of humans, rats, mice, and monkeys, [116][117][118][119][120] but thus far, no group has definitively shown that these cells are capable of producing slow waves in isolation. Furthermore, myometrial cells may not exhibit the slow waves seen in the gut.…”
Section: The Uterine Pacemakermentioning
confidence: 99%